Pengaruh Motivasi Kerja Terhadap Produktivitas Kerja Karyawan Pada Bolly Departement Store Woha - Andrian Mardiansyah; Muhammad Badar (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
This research aims to determine the effect of work motivation on employee work productivity at Woha Bolly department store. The sample in the research was 50 employees using a saturated sampling technique. Data collection techniques using observation, questionnaires and literature study. Data analysis technique using simple linear regression. The results of the research show that work motivation has a significant effect on employee work productivity at the Woha Bolly department store. Keywords: